Mental health among younger and older caregivers of dementia patients. Issue 2 (10th March 2016) - Koyama, Asuka; Matsushita, Masateru; Hashimoto, Mamoru; Fujise, Noboru; Ishikawa, Tomohisa; Tanaka, Hibiki; Hatada, Yutaka; Miyagawa, Yusuke; Hotta, Maki; Ikeda, Manabu
Abstract : Aim: Caregiver burden in dementia is an important issue, but few studies have examined the mental health of younger and older family caregivers by comparing them with age‐ and gender‐matched community residents. We aimed to compare the mental health of dementia caregivers with that of community residents and to clarify factors related to mental health problems in younger and older caregivers. Methods: We studied 104 dementia caregivers; 46 were younger (<65 years) and 58 were older (≥65 years). A total of 104 community residents who were matched for age and gender were selected. We compared depression (Center for Epidemiologic Studies Depression Scale for younger participants; Geriatric Depression Scale for older participants), health‐related quality of life (QOL) short‐form health survey (SF‐8), sleep problems, and suicidal ideation between the caregivers and community residents by age. Behavioural and psychological symptoms of dementia, activities of daily living (ADL), and instrumental ADL were assessed among patients with dementia using the Neuropsychiatric Inventory, Physical Self‐Maintenance Scale, and Lawton Instrumental ADL Scale, respectively. Results: According to SF‐8 results, both younger and older caregivers had significantly worse mental QOL than community residents (younger caregivers: 46.3 vs community residents: 49.7, P  = 0.017; older caregivers: 48.2 vs community residents: 51.1, P  = 0.024) but were not more depressive. Sleep problems were significantly more frequent in younger caregivers (39.1%) than in community residents (17.0%) ( P  = 0.017). Multiple regression analysis revealed that caregivers' deteriorated mental QOL was associated with patients' behavioural and psychological symptoms of dementia in younger caregivers and with dementia patients' instrumental ADL and female gender in older caregivers. Conclusions: Dementia caregivers had a lower mental QOL than community residents. To maintain caregivers' mental QOL, it is necessary to provide younger caregivers with skills or professional interventions for dealing with behavioural and psychological symptoms of dementia, and older caregivers must be offered adequate care support.